Determination of ethanol and acetic acid content in local brands of apple vinegar: gas chromatography test for halal requirements - Sumiyani, Ririn; Budiono, Ryanto; Khamila, Henni Matul; Pramesti, Tia Antika; Rachmaniah, Orchidea (Universitas Airlangga, 2024)
Apple vinegar is commonly made from fermented apple juice, which involves two consecutive stages of fermentation: alcoholic and acetic acid fermentation. Both Saccharomyces cerevisiae and Acetobacter acetii are involved in fermentation. Apple vinegar has various benefits, such as stabilizing blood pressure, treating rheumatism, and detoxifying toxins. Excessive consumption of this product may cause damage to the esophagus, low blood potassium levels or hypokalemia, diarrhoea, and ulcers due to the high acetic acid content. Moreover, the ethanol content also needs to be determined. It should be lower than 0,5% to fulfil the halal requirements for certification. The local brands of apple vinegar in Indonesia are generally produced by small-medium enterprises (SMEs), especially in Malang, Indonesia. Commercial brands of various apple vinegar, XCJO, YSW, THT, NTF, and BST, were sampled for their ethanol and acetic acid content in one method of analysis: gas chromatography, utilizing the high volatility properties of ethanol and acetic acid. The samples contain 17.73%, 11.45%, 6.43%, 2.67%, and 1.49% v/v of acetic acid, respectively, for XCJO, YSW, THT, NTF, and BST. At the same time, the ethanolic content is 0.11 and 0.02% v/v for XCJO and YSW, respectively, which are lower than the label value informed. Meanwhile, the rest of the brands' content is 4.00%, 2.39%, and 3.21% ethanol for THT, NTF, and BST, respectively. In addition, the acetic acid content of XCJO is high. A consumer should be aware of dilution before consuming the XCJO apple vinegar. It is unnecessary in the case of YSW, THT, NTF, and BST. Keywords: Analysis, Fermentation, Halal, Small-medium enterprises